Phylogenetic analysis of the genus Pseudoroegneria and the Triticeae tribe using the rbcL gene. (October 2015) - Gamache, Jacques; Sun, Genlou
Abstract: The Pseudoroegneria species are perennial grasses in the Triticeae tribe, whose St genome has been linked to several important polyploid species. Due to frequent hybridization and complex genetic mechanism, the relationships within Pseudoroegneria, and within the Triticeae have been heavily disputed. Using the chloroplast rbc L gene we estimated the nucleotide diversity of 8 Pseudoroegneria species. We also examined the phylogenetic relationships within Pseudoroegneria and of Pseudoroegneria within the Triticeae. The estimates of nucleotide diversity indicated that Pseudoroegneria tauri and Pseudoroegneria spicata species had the highest diversity, while Pseudoroegneria gracillima had the lowest diversity. The phylogenetic analysis of Pseudoroegneria placed all P. spicata species into a clade separate from the other Pseudoroegneria species, while the relationship of the other Pseudoroegneria species could not be determined. Due to the groupings of Pseudoroegneria with the polyploid Elymus, our results strongly supported Pseudoroegneria as the maternal genome donor to Elymus . There was also weak support that P. spicata may be the maternal donor to the StH Elymus species. Highlights: Nucleotide diversity of rbc L sequences in Pseudoroegneria species was analysed. Pseudoroegneria tauri and Pseudoroegneria spicata species had the highest, Pseudoroegneria gracillima had the lowest diversity. Phylogenetic analysis grouped all P. spicata species into a clade. The relationship of the other Pseudoroegneria species could not be determined. Triticeae phylogeny was also analysed and discussed based on rbc L sequences.